Promoting ethical governance: A collaborative framework for End-of-Life care policies for the elderly in China - Zang, Zheng; Chen, Yueqin (Acta Bioethica, 2025)
Delivering end-of-life care services to elderly patients, addressing their physical and psychological needs, enhancing their quality of life, and preserving their dignity represent not only advances in human civilization, but also crucial benchmarks for a country’s social development and justice. Effective provision of end-of-life care services hinges on robust national policies, adequate investment, and a cohesive societal effort. Clearly defining the roles and interplay between the government and society is paramount. This study examines China’s end-of-life care policies through an ethical lens, aiming to elucidate the nation’s stance on national and societal duties and ethical dynamics in end-of-life care development. The research reveals that, ethically, China’s end-of-life care services require enhancements in legislative empowerment, regulatory oversight, financial backing, and the functioning of social entities. The absence of government and societal functions, along with inadequate collaboration and synergy between the two sectors, has led to incomplete fulfillment of the diverse end-of-life needs of the elderly. Consequently, China’s end-of-life care sector should strive for a transparent delineation of responsibilities between the government and society, as well as precise ethical positioning.